Pendidikan Anak Usia Dini menurut Al-Qur’an dan Hadis: Fondasi Strategis bagi Pengembangan Pendidikan Berkelanjutan - Muchasin, Fiki Vendi; Anshori, Muhammad Isa (TSAQOFAH, 2025)
This study is motivated by the limited scholarly attention to early childhood education (PAUD) from an Islamic theological perspective, despite its strategic role in laying the foundation for sustainable educational development. The objective of this research is to explore the concept, methods, and strategic relevance of PAUD according to the Qur’an and Hadith. Using a qualitative approach, the study analyzes twelve classical and contemporary Islamic texts selected through purposive sampling. Data were collected through document analysis and examined using thematic content analysis, referencing tafsir, sharh hadith, and Islamic educational theory. The findings reveal that Islam emphasizes the significance of early childhood education as a critical phase for instilling tawhid, moral values, and a lifelong learning orientation. This concept aligns with the goals of early character development and educational continuity. The study concludes that PAUD plays a vital role in preparing children intellectually, emotionally, and spiritually, forming the foundation for subsequent educational stages. The implications of this research include theoretical contributions to Islamic pedagogy and early childhood education literature, as well as practical recommendations for educators, policymakers, and parents in designing PAUD programs that integrate Islamic values with developmentally appropriate approaches. Furthermore, this research opens avenues for future studies on integrating Islamic PAUD frameworks with national curricula and teacher training programs.